THE EFFECTIVENESS OF THE USE OF INNOVATIVE METHODS IN THE TEACHING OF CYTOLOGY HISTOLOGY EMBRYOLOGY IN THE TREATMENT UNIT - Tursunbabaeva Malika Xafizovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article explores the effectiveness of innovative teaching methods in the medical training of cytology, histology, and embryology. It highlights how technology-enhanced learning approaches, such as digital simulations, virtual microscopy, and interactive learning platforms, impact student understanding and retention. A comparative analysis with traditional methods is provided, and the article discusses challenges and strategies for successful implementation. Results indicate that these methods significantly enhance students' ability to grasp complex concepts, fostering improved clinical decision-making.